Seroprevelance of Blood Borne Viruses among Patients Attending Hospital for Surgery in Najaf - Obaid, Sajad saad kashan; jasim, Noor alhuda qahtan adnan; younis, Karar abd alhussain (American Journal of Biology and Natural Sciences, 2025)
The current study is hospital based descriptive cross sectional one and conducted during the period of 1/1/2023 to 1/11/2023 among patients attending to the Al-Sadir teaching hospital of Najaf, Iraq. To estimate the prevalence of the blood borne viruses like Hepatitis B virus ,Hepatitis C virus and human immune deficiency virus. Blood samples were taken from the patients as a routine laboratory viral pre-surgical management screening tests by ELISA. Data were analyzed and exhibited in that hepatitis B virus is more prevalent among the positive results in addition with Hepatitis C virus and Human immune deficiency virus. The results are representing the cumulative number of cases covering the period of 10 months in only one hospital of Najaf in regardless to the ages. The majority of the positive cases are males distributed as 64(56.6%)HBV, 60 (55%) HCV and 7(70%) HIV compared to the positive cases of females as 49(43.4%),42(45%) and 3(30%) respectively. Evenmore the such viral screening tests were reported as 225 positive out of 19925 blood samples.